PENTINGNYA LABORATORIUM FISIKA DI SMA/MA DALAM MENUNJANG PEMBELAJARAN FISIKA - sarjono, sarjono sarjono (Madaniyah, 2018)
ABSTRACT           Physics is seen as an important lesson to be taught as a separate subject with some considerations. There are two important things that are interrelated and inseparable in the study of physics, namely the study of theory and observation in the physics lab. Both can not be separated from each other, interdependence and mutual filling. Physics is seen as a process and a product so that the success of physics learning should consider effective and efficient learning. Physics lessons provide learning supplies to learners, as a means to cultivate and develop students thinking skills. This thinking ability is useful for continuing education to a higher level, also useful for solving problems encountered in everyday life. One of the factors that greatly support the success of physics education is the laboratory. Through practicum activities in the laboratory can be shown natural phenomena and physics concepts are discussed in the classroom, can be demonstrated and proven. Besides, practicum activities can foster independent attitude, scientific attitude, interest, honesty and practice psychomotor skills among learners.Keywords: laboratory, physics lab